Preparation of a hands-on tutorial teaching basics of Mainframe ISPF programming - Vašák, Michal; Pecinovský, Rudolf, 1954-; Forman, Miloš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
This paper is primarily focused on developers wanting to learn the essentials of developing mainframe applications on the IBM`s Interactive System Productivity Facility (ISPF) platform. It describes the components of the ISPF environment, focusing mainly on the two components most used in mainframe application development: The ISPF Dialog Manager and the ISPF Program Development Facility (PDF). Second part of the paper is a hands-on tutorial, where the reader is guided trough the creation of a set of simple interactive ISPF applications, with focus on covering the most used features of the platform. Within the paper it is assumed that any reader interested in this topic has basic mainframe skills and knowledge, including user knowledge of ISPF PDF, as it is usually the primary tool for dataset manipulation and editing in the z/OS mainframe environment. A wider skill set is assumed for readers who want to go through the tutorial, for example REXX and z/OS assembler basics. However none of these skills are necessary, nor expected, from those who are mainly interested in finding out what ISPF is and what it can offer to z/OS applications and their developers.
Vedoucí práce: Rudolf Pecinovský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses